Conserve primers for sequencing complete ungulate mitochondrial cytochrome c oxidase I (COI) gene from problematic and decomposed biological samples. Issue 1 (1st January 2017) - Kumar, Ajit; Ghazi, Mirza Ghazanfar Ullah; Singh, Bhim; Hussain, Syed Ainul; Bhatt, Dinesh; Gupta, Sandeep Kumar
Abstract: We describe six novel ungulate-specific conserved primers for sequencing the complete mitochondrial cytochrome c oxidase I (COI) gene of selected threatened species from degraded samples for effective conservation planning. These primers amplified 301–1599 bp DNA fragments in various combinations. The method described may assist in the sequencing of either complete gene from moderate to good quality DNA or shorter fragment from degraded DNA.